The Handbook of Plant Biosecurity Principles and Practices for the Identification, Containment and Control of Organisms that Threaten Agriculture and the Environment Globally - Gordh, Gordon; McKirdy, Simon (Springer Netherlands : Imprint: Springer, 2014)
The Handbook is arranged in 23 chapters written by 85 world experts who systematically explain the substance of Plant Protection (Biosecurity). The Handbook is the first comprehensive treatment of regulations, policies and procedures used to protect domestic agriculture and natural resources from attack by invasive alien species via international trade and travel. Case studies explain complex regulatory programs involving significant invasive organisms, including insects, plant pathogens and weeds.